COVID 19 pandemic and manipulation technologies - Sukhara Viktoriia (My University, 2023)
The purpose of the work - to determine the main mechanisms of manipulative influence in media discourse on the example of manipulation of Covid-19. Object of research: selected materials of media discourse on the example of manipulation of Covid-19. Subject of research: the mechanisms used to first attract the attention of the recipient, and then - to manipulate the consciousness of a large audience. Research methods. To realize the purpose and objectives of the thesis were used general and special methods, in particular: analytical-synthetic; inductive - to generalize and systematize the conclusions. The practical significance of the work is that its results can be used in the study of linguistics and translation studies, in writing essays, term papers.
Keywords: Covid-19; media discourse; manipulative influence